EDUKASI DAMPAK NEGATIF PENGGUNAAN GADGET DAN MEDIA INTERNET YANG BERLEBIHAN BAGI ANAK-ANAK - Muhammad Sholeh; Rr. Yuliana Rachmawati; Dina Andayati (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
One of the impacts of the COVID-19 pandemic is the implementation of the online teaching and learning process. This is one of the factors that causes dependence on the internet to be higher. The implementation of online learning makes the use of gadgets connected to the internet for children more often. So that children can use the internet properly and safely, it is necessary to have supervision and assistance from parents. This community service given to mothers in the Baros Pakanewon hamlet of Kretek Bantul aims to provide knowledge about safe and healthy internet use for children. The implementation method is carried out by giving questionnaires regarding the use of gadgets in children and lectures on the negative and positive impacts of internet use for children. The results of the implementation of community service carried out include educating mothers on strategies so that children do not depend on gadgets and how the role of parents specifically for mothers is in providing assistance to children in using gadgets that are connected to the internet. Evaluation of activities was carried out by giving a questionnaire and the results of the questionnaire on the question of the bad impact of using gadgets to damage the future of children showed that 85% answered strongly agree and 15% answered agree. The results of the questionnaire on the question of the negative impact on children's health, 90% answered strongly agree and 10% answered agree.